IMPLEMENTASI MAKNA SAKRAMEN EKARISTI DALAM KEHIDUPAN KELUARGA KATOLIK DI STASI SANTO TARSISIUS NAMO PULI PAROKI SANTO YOSEF DELITUA - Tarigan, Putri Damiana Br; Fajariyanto, Tri Chandra (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The sacrament of the Eucharist holds a central position in the Catholic faith as a source of spiritual strength and a means of union with Christ. However, the reality on the ground often reveals a gap between theological understanding and the practical experience of the congregation in their daily lives. This study aims to explore in depth the implementation of the meaning of the Eucharist in the lives of Catholic families at the Santo Tarsisius Namo Puli Station, Santo Yosef Delitua Parish, amidst the challenges of modernization. The method used was descriptive qualitative, with data collected through participatory observation, in-depth interviews, and documentation studies of families at the station. The research findings indicate that the congregation has a strong liturgical understanding, reflected in their discipline and reverence during the celebration of the Eucharist. Concretely, these spiritual values ??are deeply ingrained and transformed into social piety, such as increased solidarity, empathy, and selfless acts of charity in the surrounding community. The Eucharist has also proven to be effective as a glue for social cohesion, uniting the congregation without barriers of status, and serves as a foundation for families instilling the moral values ??of honesty and a spirit of service. The main conclusion emphasizes that for this community, the Eucharist is not just a ritual, but the heart of spiritual life, empowering families to remain resilient, harmonious, and faithful in living out their faith amidst the dynamics of the times. ABSTRAK Sakramen Ekaristi menempati posisi sentral dalam iman Katolik sebagai sumber kekuatan spiritual dan sarana persatuan dengan Kristus, namun realitas di lapangan kerap menunjukkan adanya kesenjangan antara pemahaman teologis dan penghayatan praktis umat dalam kehidupan sehari-hari. Penelitian ini bertujuan untuk menggali secara mendalam implementasi makna Ekaristi dalam kehidupan keluarga Katolik di Stasi Santo Tarsisius Namo Puli, Paroki Santo Yosef Delitua, di tengah tantangan arus modernisasi. Metode yang digunakan adalah kualitatif deskriptif dengan pengumpulan data melalui observasi partisipatif, wawancara mendalam, dan studi dokumentasi terhadap keluarga-keluarga di stasi tersebut. Temuan penelitian menunjukkan bahwa umat memiliki penghayatan liturgis yang tinggi, yang tercermin dari kedisiplinan dan kekhusyukan saat perayaan Ekaristi. Secara konkret, nilai spiritual ini tertanam kuat dan bertransformasi menjadi kesalehan sosial, seperti meningkatnya solidaritas, empati, serta tindakan amal kasih tanpa pamrih di lingkungan sekitar. Ekaristi juga terbukti berfungsi efektif sebagai perekat kohesi sosial yang menyatukan umat tanpa sekat status, serta menjadi fondasi bagi keluarga dalam menanamkan nilai moral kejujuran dan semangat pelayanan. Simpulan utama menegaskan bahwa bagi komunitas ini, Ekaristi bukan sekadar ritual, melainkan jantung kehidupan rohani yang memberdayakan keluarga untuk tetap tangguh, harmonis, dan setia menghidupi iman di tengah dinamika zaman.